The effect of MHD on free convection with periodic temperature and concentration in the presence of thermal radiation and chemical reaction - Zigta, Binyam; Koya, P.R. (Zielona Góra: Uniwersytet Zielonogórski)
This paper studies the effect of magneto hydrodynamics on unsteady free convection between a pair of infinite vertical Couette plates. The temperature of the plates and concentration between the plates vary with time. Convection between the plates is considered in the presence of thermal radiation and chemical reaction. The solution is obtained using perturbation techniques. These techniques are used to transform nonlinear coupled partial differential equations to a system of ordinary differential equations. The resulting equations are solved analytically. The solution is expressed in terms of power series with some small parameter.
Keywords: MHD; unsteady free convection; thermal radiation; chemical reaction; Couette porous plates